Peroneal Nerve Palsy due to Bulky Osteochondroma from the Fibular Head: A Rare Case and Literature Review - T. Cherrad; M. Bennani; H. Zejjari; J. Louaste; L. Amhajji (Case Reports in Orthopedics)
Common peroneal neuropathy is the most common compressive neuropathy in the lower extremities. The anatomical relationship of the fibular head with the peroneal nerve explains entrapment in this location. We report the case of a 14-year-old boy admitted with a left foot drop. The diagnosis was an osteochondroma of the proximal fibula compressing the common peroneal nerve. The patient underwent surgical decompression of the nerve and resection of the exostosis. Three months postoperatively, there was a complete recovery of the deficits. The association of osteochondroma and peroneal nerve palsy is rare. Early diagnosis is required in order to adjust the management and improve the results. It is worth to underscore that surgical resection is proven to be the appropriate treatment method ensuring high success rates.